Sexueller Missbrauch von Kindern durch katholische Priester seit 2009: Verlauf und relative Häufigkeit im Vergleich zur männlichen Allgemeinbevölkerung - Dreßing, Harald; Dölling, Dieter; Hermann, Derik; Horten, Barbara; Hoell, Andreas; Voss, Elke; Salize, Hans Joachim (Psychiatrische Praxis, 2019)
Objective: This paper explores the frequency of sexual abuse allegations against Catholic priests and deacons in the years 2009 to 2015 in relation to the male general population in Germany.